Bridging Technology and Quality: A Systematic Review of Information System (IS) Effectiveness in Enhancing Tax Audit Quality - Nor Asiah Taib; Izlawanie Muhammad; Suhaila Abdul Hamid (Global Academic Excellence (M) Sdn Bhd, 2026)
Tier 3- Indexed by MyCite